Análise do discurso judicial em relação à mulher em situação de violência doméstica nos acórdãos do Tribunal de Justiça do Estado do Maranhão - MENDES, Tatiana Amélia Soares Pinheiro (2021)
Ensuring a fair trial of cases related to violence against women suggests analyzing them under the new hermeneutic paradigm that comprises gender relations. This research focuses on the analysis of the discourse contained in the judgments of the Court of Justice in the State of Maranhão, as the highest instance in the state of power-knowing, from the collection and analysis of data on the decisions handed down in the Criminal Chambers of the TJMA in the processes of domestic and family violence in the State. Violence against women is understood as actions or omissions based on gender that cause death, harm, physical, sexual or psychological suffering, both in public and private circles. It reveals, according to international organizations, a real violation of human rights and fundamental freedoms. In Brazil, domestic and family violence against women became naturalized in such a way that for a long time it was treated as a private problem to be solved between the parties, far from public instances of solving problems of this nature when it was not a question of women. After the creation of Law no. 11.340/2006, popularly known as Lei Maria da Penha, responsible for creating mechanisms to curb and prevent domestic and family violence against women, there was a profound and constant change in the social and national context. In this sense, we seek to discuss the importance of gender as a category of analysis for understanding the Brazilian social reality under this new paradigm in studies on the performance of the Justice System, in this case Criminal, as a way of confronting violence and discrimination against the woman, from the dialogue between Criminal Sciences and other branches of knowledge such as Sociology and French Discourse Analysis. Still, aiming to understand the ideological underpinnings that support the judicial theses, despite the supposed neutrality of the decisions, in order to try to scientifically contribute to the Justice System and its jurisdictional provision.